2019
DOI: 10.1002/jcp.28500
|View full text |Cite
|
Sign up to set email alerts
|

Sirt6 deletion in hepatocytes increases insulin sensitivity of female mice by enhancing ERα expression

Abstract: Sirtuin 6 (Sirt6), a NAD+‐dependent protein deacetylase, is involved in hepatic glucose metabolism and insulin sensitivity, which impact metabolic homeostasis. In this paper, we discover that Sirt6 affects the insulin sensitivity of mice in a gender‐dependent manner; few studies have been conducted on this issue. Based on reports revealing the influences of sex hormones on insulin signaling, this investigation explores the mechanism by which Sirt6 regulates the estrogen pathway and disrupts insulin signal tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Furthermore, it has been regarded as a therapeutic agent for IR [ 26 , 27 ]. SIRT6 deficiency could make diet-induced IR heavier [ 28 ]. SIRT6 has been well established to promote nuclear factor erythroid 2-related factor 2 (Nrf2) binding the antioxidant response elements (AREs) and to protect cells from oxidative stress [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been regarded as a therapeutic agent for IR [ 26 , 27 ]. SIRT6 deficiency could make diet-induced IR heavier [ 28 ]. SIRT6 has been well established to promote nuclear factor erythroid 2-related factor 2 (Nrf2) binding the antioxidant response elements (AREs) and to protect cells from oxidative stress [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, hepatic SIRT6 reduced p300 to downregulate the protein level of estrogen receptor ERα, and thus attenuated estrogen‐induced activation of PI3K and blocked insulin signal transduction to eventually reduce insulin sensitivity in the liver. Consistently, SIRT6 deletion in hepatocytes significantly increased insulin sensitivity, especially in female mice, by improving the expression of ERα 183 …”
Section: Human Diseasesmentioning
confidence: 64%
“…Along this line, the protective function of SIRT6 is regulated by nicotinamide mononucleotide adenylyltransferase 2 (Nmnat2), whose overexpression increases the intracellular NAD + level and then augments cardiomyocytes hypertrophic prevention by activating SIRT6 204 . SIRT6 was also observed to suppress PI3K/Akt signaling to reduce p300 expression via promoting its degradation 183,205,206 . The downregulation of p300 protein subsequently inhibited the transcriptional activity of NF‐κB p65 subunit, hence protecting cardiomyocytes from hypertrophy by angiotensin II (Ang II) or phenylephrine stimulation 205,207 .…”
Section: Human Diseasesmentioning
confidence: 99%
“…For example, deletion of Sirt6 in adipose tissues decreased lipolysis and thermogenesis, leading to obesity 19,38 ; hepatic‐specific deletion of Sirt6 aggravated liver steatosis and insulin resistance, 16,39 but moderate and physiological overexpression of Sirt6 enhanced insulin sensitivity in skeletal muscle and liver 40 . However, studies also showed that Sirt6 inhibition significantly improved glucose tolerance in a type 2 diabetes mouse model, 41 and Sirt6 deletion in hepatocytes increased insulin sensitivity of female mice 42 . In the present study, Sirt6 overexpression specifically in hypothalamic POMC neurons exacerbated energy imbalance and metabolic disorders.…”
Section: Discussionmentioning
confidence: 99%